Agronomic evaluation of quinoa genotypes (Chenopodium quinoa Willd.) in agroclimatic conditions in the Mocache zone - Mestanza Uquillas, Camilo (2019)
Quinoa (Chenopodium quinoa Willd.) has been cultivated mainly in the Andean mountain range in Bolivia, Peru, Ecuador and Colombia, it was one of the main foods of the pre-Inca and Inca peoples. The benefits of quinoa lie in its high nutritional value with a protein content and its great phenotypic plasticity. The present investigation was carried out in the Experimental Farm “La María” of the State Technical University of Quevedo, located in the Province of Los Ríos. The objective of the work was to analyze the agronomic characteristics of quinoa genotypes in environmental conditions of the central coast. A completely randomized design was applied with 21 treatments (genotypes) and three repetitions. The agronomic variables evaluated showed significant statistical differences (p <0.05). In the height variable of the plant it highlighted genotype 48 with 154.17 cm to 90 days. On the other hand, in the determination of days to harvest the latest genotype was RGG genotype with 143 days, while the earliest genotype was 42 with 90 days to harvest. Variable weight of 1,000 seeds the results showed that the genotype Faro 2 pointed out slightly with a record of 2.58 g. Finally, in terms of performance per plant (g) the largest recorded genotype obtained it O-5 with 143.15 g plant-1. The data recorded in the different variables demonstrate viability in the production of quinoa and due to its wide adaptability, make it a valuable diversification alternative for the coastal region.